Everyday urbanisms in the pandemic city: a feminist comparative study of the gendered experiences of Covid-19 in Southern cities. (16th March 2023) - Razavi, Nasya S.; Adeniyi-Ogunyankin, Grace; Basu, Swagata; Datta, Anindita; de Souza, Karen; Ting Ip, Penn Tsz; Koleth, Elsa; Marcus, Joy; Miraftab, Faranak; Mullings, Beverley; Nmormah, Sylvester; Odunola, Bukola; et al.
ABSTRACT: Drawing on GenUrb's comparative research undertaken in mid-2020 with communities in five cities—Cochabamba, Bolivia, Delhi, India, Georgetown, Guyana, Ibadan, Nigeria, and Shanghai, China—we engage in an intersectional analysis of the gendered impacts of the Covid-19 pandemic in women's everyday lives. Our research employs a variety of context-specific methods, including virtual methods, phone interviews, and socially-distanced interviews to engage women living in neighbourhoods characterized by underdevelopment and economic insecurity. While existing conditions of precarity trouble the before-and-after terminology of Covid-19, across the five cities the narratives of women's everyday lives reveal shifts in spatial-temporal orders that have deepened gendered and racial exclusions. We find that limited mobilities and the different and changing dimensions of production and social reproduction have led to increased care work, violence, and strained mental health. Finally, we also find that social reproduction solidarities, constituting old and new circuits of care, have been reinforced during the pandemic.